1989
DOI: 10.1038/jcbfm.1989.69
|View full text |Cite
|
Sign up to set email alerts
|

The C15O2 Build-up Technique to Measure Regional Cerebral Blood Flow and Volume of Distribution of Water

Abstract: Summary:A new method to measure regional CBF (rCBF) and volume of distribution of water is presented. It centres on recording the tissue build-up and retention of ISO-labelled water during the continuous inhalation of ISO-labelled carbon dioxide. Simultaneously, the arterial concentration is continuously monitored, and corrections for delay and dispersion in the recorded response are made by curve fitting. The values for the volume of disSeveral tracers have been proposed for the mea surement of regional CBF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The C1502 buildup technique has been studied by Lammertsma et al (25). Unpublished work in the Massachusetts General Hospital PET laboratory has confirmed that the integrated counts over inhalation periods up to 90 sec is a linear function of the flow over the expected range; that is, the amount of radiation that gets into tissue is proportional to blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…The C1502 buildup technique has been studied by Lammertsma et al (25). Unpublished work in the Massachusetts General Hospital PET laboratory has confirmed that the integrated counts over inhalation periods up to 90 sec is a linear function of the flow over the expected range; that is, the amount of radiation that gets into tissue is proportional to blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…Errors due to tissue heterogeneity are small (less than 10%) in these methods (Herholz and Pat lak, 1987); as for errors due to time shifts and dis persion of input functions, only limited data are available, but in theory they can be modeled and accounted for (Lammertsma et a!. , 1986(Lammertsma et a!. , , 1987c.…”
Section: Measurement Of Cerebral Blood Flow Principles and Methodsmentioning
confidence: 99%
“…In contrast to the Recently, a new method has been described for the measurement of CBF using inhalation of C1502 and positron emission tomography (PET) (Lam mertsma et aI., 1990). This method involves two separate steps in generating reproducible functional CBF images, which are required in the analysis of activation or stimulation studies.First, the dynamic PET frames collected during and after inhalation of C1502 are analyzed using a nonlinear regression technique to obtain accurate estimates of delay and dispersion of the arterial blood curve (Lammertsma et al, 1989). Second, us ing these values of delay and dispersion, a pixel-by pixel integral analysis is then applied to the inhala tion (buildup) phase.…”
mentioning
confidence: 99%
“…First, the dynamic PET frames collected during and after inhalation of C1502 are analyzed using a nonlinear regression technique to obtain accurate estimates of delay and dispersion of the arterial blood curve (Lammertsma et al, 1989). Second, us ing these values of delay and dispersion, a pixel-by pixel integral analysis is then applied to the inhala tion (buildup) phase.…”
mentioning
confidence: 99%